TRANSPARENCY IN MARKETS FOR EXPERIENCE GOODS: EXPERIMENTAL EVIDENCE. (31st August 2014) - Henze, Bastian; Schuett, Florian; Sluijs, Jasper P.
<x xml:space="preserve">Abstract</x> We propose an experimental design to investigate the role of information disclosure in the market for an experience good. The market is served by a duopoly of firms that choose both the quality and the price of their product. Consumers differ in their taste for quality and choose from which firm to buy. We compare four different treatments in which we vary the degree to which consumers are informed about quality. Contrary to theoretical predictions, firms do not differentiate quality under full information. Rather, both tend to offer products of similar, high quality, entailing more intense price competition than predicted by theory. Under no information, we observe a "lemons" outcome where quality is low. At the same time, firms manage to maintain prices substantially above marginal cost. In two intermediate treatments, quality is significantly higher than the no‐information level, and there is evidence that prices become better predictors of quality. Taken together these findings suggest that information disclosure is a more effective tool to raise welfare and consumer surplus than theory would lead one to expect. (JEL L15, C91, D82)